Factors affecting the role of local councils in local policy-making - Rushdi Aziz Abdullah (Review of Economics and Political Science (REPS), 2019)
Purpose - The purpose of this paper is to examine empirically the relevance and impact of a number of factors on the role of local councils in local policy-making in Erbil province/Iraq. Design/methodology/approach - This research theoretically based on literature review and adopted an analytical approach to clarify the related concepts through the policy cycle approach. On the empirical side, the research adopted a descriptive analysis for research questions and used statistical analysis to test the research hypotheses. Findings - The results of the study reveal that variables of the local policy-making process, political factors, interaction patterns and the role of other actors have relevance in the role of local councils. In addition, the study concludes that technical feasibility, budgetary considerations, public opinion, coalition building, civil society, executive bodies, administrative organs and non-governmental organizations have a positive effect on the role of local councils in local policy-making in Erbil province, while interest groups have a negative effect on the role of local councils in local policy-making in Erbil province. Practical implications - The findings and recommendations of this research can practically use by the local councils to achieve effective local policy, particularly in Erbil province/Iraq. Originality/value - This research has interesting implications in theory and practice, as it provides several contributions to the literature, as well as the practical contribution for local councils in the local policy-making process.
Keywords: 330; Political factors; Local councils; Interaction patterns; Erbil province/Iraq; Local official and unofficial actors; Local policy-making process